Rural Communities as Agents Forming Religious Character in Education: A Socio-Cultural Perspective - Itmamul Fahmi; Tutuk Ningsih; M. Slamet Yahya (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study examines in depth the process of religious character formation in rural communities through a socio-cultural approach. In the context of Indonesian society, rural environments have great potential as agents of religious education due to strong communal ties, preservation of local culture, and high participation in religious practices. This article highlights the strategic role of the family as a primary socialization agent, religious figures as informal leaders who provide spiritual and moral guidance, and Islamic educational institutions such as Islamic boarding schools (pesantren) and madrasahs (madrasahs) as centers for the internalization of religious values. Furthermore, local cultures such as mutual cooperation (gotong royong) and deliberation (musyawarah) also serve as vehicles for the instillation of contextual moral values. Through a qualitative approach and literature review, it was found that the integration of formal and non-formal education, social control based on religious norms, and the wise use of digital media can strengthen the formation of religious character in the younger generation. This study emphasizes the importance of religious character education that is adaptive to current developments, while remaining rooted in traditional values and religious moderation. The results of this study provide a conceptual contribution to the development of community-based character education models in addressing global challenges and moral crises. However, it is important to note that social media also has a significant impact on the education and socialization process of the younger generation.